Effectiveness of SenAR augmented reality model on students’ forward roll skills development - Sri Gusti Handayani; Dwiprima Elvanny Mayori; Hendri Neldi; Anton Komaini; Heru Andika (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Low forward roll proficiency among students is often caused by limited instructional approaches that rely on verbal explanations and demonstrations, making it difficult to understand movement sequences. This study aimed to examine the effect of the Augmented Reality-based SenAR learning model on students’ forward roll skills. A quasi-experimental pretest–posttest control group design was used, involving 68 university students aged 18–20 years. Participants were divided into experimental and control groups. Forward roll performance was assessed using a structured performance rubric. The experimental group received SenAR-based training, while the control group used conventional methods. Data were analyzed using independent t-test after normality and homogeneity assumptions were met. Results showed a significant difference between groups (p < 0.001), with the experimental group achieving higher post-test scores (M = 38.24) than the control group (M = 35.03). These findings suggest that SenAR improves students’ movement understanding and execution. However, the short intervention duration and limited sample should be considered in interpreting the results.